2009
DOI: 10.1002/ijc.24312
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous steroid hormone levels in early pregnancy and risk of testicular cancer in the offspring: A nested case–referent study

Abstract: According to the leading hypothesis on testicular cancer (TC) etiology exposure to a specific pattern of steroid hormones in utero, in particular, to high levels of estrogens and low levels of androgens is the major determinant of TC risk in the offspring. We performed a case-referent study nested within Finnish, Swedish and Icelandic maternity cohorts exploiting early pregnancy serum samples to evaluate the role of maternal endogenous steroid hormones with regard to the risk of TC. TC cases and referents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…This hypothesis also includes a possible role for endogenous and exogenous hormones or hormone-like substances (endocrine disruptors) mainly acting as estrogens or anti-androgens. Although direct evidence in humans is lacking, numerous animal models support this notion (Sharpe 2003, Sharpe & Skakkebaek 2008, and associations of TGCT with maternal estrogen and androgen levels in early pregnancy have been reported (Holl et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis also includes a possible role for endogenous and exogenous hormones or hormone-like substances (endocrine disruptors) mainly acting as estrogens or anti-androgens. Although direct evidence in humans is lacking, numerous animal models support this notion (Sharpe 2003, Sharpe & Skakkebaek 2008, and associations of TGCT with maternal estrogen and androgen levels in early pregnancy have been reported (Holl et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Probably, a combination of high gonadotropin levels coupled with unbalanced androgen/estrogen levels and/or activity is the key event for TGCT development and progression (Garolla et al 2005, Rajpert-De Meyts 2006. Supporting this hypothesis, recently an association of TC with maternal estrogen and androgen levels in early pregnancy has been reported (Holl et al 2009). In addition, exposure to endocrine-disrupting chemicals acting as either weak estrogen agonist or androgen antagonist via binding to the estrogen and androgen receptors has been suggested to be associated with the risk of TGCT and other reproductive disorders (Wohlfahrt-Veje et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…These factors suggest that initial steps in TGCC development take place during embryogenesis. Increased exposure to estrogens or anti-androgens is the proposed common denominator, but studies show inconsistent results, and a final conclusion cannot be made yet [McGlynn et al, 2005;Holl et al, 2009;Kortenkamp et al, 2014]. Together, these genetic and environmental risk factors are translated into a number of clinical characteristics such as family occurrence, infertility, cryptorchidism, urological anomalies, and DSD with a lifetime risk of 25% (in the presence of GBY [gonadoblastoma region on the Y chromosome], see below) [Rijlaarsdam and Looijenga, 2014].…”
Section: Environmental and Clinical Risk Factorsmentioning
confidence: 99%
“…The actions of luteinizing hormone (LH) are critical for postnatal Leydig cell differentiation (Saez, 1994), and it is known that Leydig cell function is indeed impaired in testes with CIS (Petersen et al, 1999). In the fetal human testis, ERβ is expressed in peritubular myoid cells, fetal Leydig cells and gonocytes (O'Donnell et al, 2001;Saunders et al, 1998) and a high intrauterine oestrogen level has been suggested as a risk factor for testicular cancer in humans (Holl et al, 2009;Rajpert-De Meyts and Skakkebaek, 1993;Sharpe and Skakkebaek, 1993;Storgaard et al, 2006) as well as in rodents (Newbold et al, 1987). Oestrogens are able to stimulate proliferation of rat neonatal gonocytes in vitro (Li et al, 1997), induce spermatogenesis in hypogonadal mice (Ebling et al, 2000), and prevent apoptosis of human adult post-meiotic germ cells (Pentikainen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this hypothesis, an association of TGCC with maternal oestrogen and androgen levels in early pregnancy has been reported recently (Holl et al, 2009). Although the mechanisms are unknown, it has been suggested that an early arrest of gonocyte differentiation, followed by increased proliferation could result in impaired cell division and accumulation of genomic aberrations (Rajpert-De Meyts, 2006), leading to the formation of transformed pre-carcinoma in situ (CIS) cells, also known as intratubular germ-cell neoplasia unclassified Skakkebaek et al, 1982).…”
Section: Introductionmentioning
confidence: 94%